Juridinių asmenų nemokumo procesas: Monografija - Jokubauskas, Remigijus (Wydawnictwo Księgarnia Akademicka, 2022)
This book focuses on the issues related to effectiveness of corporate insolvency proceedings. In Lithuania the latest reform of corporate insolvency proceedings was implemented in 2019 following the adoption of the Law on Insolvency of Enterprises (thereinafter – LIE) which reformed restructuring and bankruptcy proceedings and replaced the Law on Bankruptcy proceedings of Enterprises (thereinafter – LBE) and the Law on Restructuring of Enterprises (thereinafter – LRE). Therefore, the legislator repealed two laws governing insolvency proceedings and established single insolvency proceedings for bankruptcy and restructuring. According to the regulation of insolvency proceedings established in Lithuania, only judicial methods of resolving insolvency disputes are recognized, since both restructuring and bankruptcy (except for the out-of-court bankruptcy of a company) cases are heard in the court. Also, the recent case law of Lithuanian courts shows that in insolvency disputes the courts shall ensure, by available means, efficiency of the proceedings and, in exceptional circumstances, intervene in matters falling within the competence of creditors.